Host suitability of soybean and corn genotypes to the root lesion caused by nematode under natural infestation conditions - Rios,Anderli Divina Ferreira (2016)
ABSTRACT: Among the nematode management strategies, genetic resistance is one of the most appropriate and desirable. However, resistant soybean and corn genotypes resistant to Pratylenchus brachyurus are not available up to the moment. The objective of this study was to evaluate the host suitability of 50 soybean and 38 corn genotypes to P. brachyurus under natural infestation. Soybean genotypes BRSGO Chapadões, BRSGO Paraíso, M-Soy 7211 RR, M-Soy 8008 RR, Emgopa 313 RR, M-Soy 8411, BRSGO Juliana RR, Emgopa 316 RR, BRSGO Luziânia RR and TMG 103 RR, and corn genotype Agromem 30A06 reduced the nematode population during the evaluation period.